Promotion of sexual health among seniors in the self-help media realm of popular culture - Bieńko, Mariola (Anthropological Review, 2015)
The issue of seniors’ sexuality, especially the aspect of sexual activity undertaken by people considered “old” is usually met with silence or even condemned. The stereotypical assumptions are that with age a person’s needs associated with feeling and realizing their own sexuality dissipate, and seniors are perceived as asexual beings. Only in the last decades of the XX century did this area of “taboo” become the subject of in-depth scientific interest and research. The average life span is increasing, and as research shows, so is the number of people who are sexually active and satisfied with intercourse at an elderly age. For hundreds of years, in Western culture, sexual health was equated with reproductive ability. The contemporary concept of health emphasizes that it is a value which allows a person to realize aspirations regardless of age. This article focuses on the content of guides which bring up the importance of seniors’ sexual health. The aestheticization characteristic of the late modern period forces a deconstruction of the concept of old age. In the rhetoric of the everyday and the narcissistic style of the realm of experts, experiencing old age simultaneously becomes a source of pleasure, as well as frustration on the road to an individual’s self-realization and self-creation.